Economic determinants concerning corporate tax revenue - Alena Andrejovská; Jozef Glova (Economies, 2023)
This study quantifies the impact of selected economic determinants on corporate tax revenues. The methodology applies a panel regression method with the 27 EU Member States considered for 2004-2020. This paper used a panel regression model with fixed effects, and the Arellano adjustment was used to achieve robust standard deviations. Source data were obtained from the European Commission, Eurostat, World Bank and Transparency International databases. Based on this hypothesis, we wanted to prove that the nominal tax rate, which is legislatively determined based on political consensus, is a decisive determinant of the amount of tax revenue. However, the analysis results reject this hypothesis, although the model showed it as positive but statistically insignificant. On the other hand, an interesting research result is that the analysis confirmed the effective tax rate as a significant determinant of tax revenues. From this, we can conclude that policies should be aimed at an effective tax rate or a better harmonisation of the nominal tax rate towards the effective rate.
Keywords: 330; corporate tax revenues; trade openness; macroeconomic determinants; effective tax rate